Application of AHP technique - Podvezko, Valentinas (Journal of Business Economics and Management, 2009)
Recently, the use of multicriteria quantitative evaluation methods for solving social and economic problems has grown considerably. One of two major components of quantitative multicriteria evaluation methods strongly influencing the evaluation results is associated with the criteria weights. In practice, the criteria weights are determined in assessing the economic development of the state and its regions, the commercial activity and strategic potential of enterprises, the effectiveness of particular investment projects, etc. Several theoretical and practical methods of determining the significance (weight) of criteria by experts are known. Pairwise comparison of criteria is widely applied, and the most well‐known, widely applied and mathematically grounded technique is the so‐called Analytic Hierarchy Process (AHP). However, the application of this method is limited because of a great number of evaluation criteria, contradicting expert estimates and incompatible matrices obtained. In the present paper, the application of AHP technique to more complicated cases is considered and some algorithms are offered.First Publish Online: 09 Jun 2011